Salvadoran returnee migrants - VASQUEZ SOSA, Alejandra Carolina (KDI School, 2023)
This research investigated the effects and importance of migration dynamics in El Salvador, emphasizing returning migrants. It also studies the importance and significance of labor mobility programs and their advantages to migrant workers going into the United States of America borders. The central part of this research was focused on returning migrants that have been going to the United States since the early 2000s with the establishment of a labor mobility program in El Salvador in recent years. This labor migration flow has increased along with the demand for Salvadoran workers to supply a workforce shortage in this northern country. However, this higher demand will represent a higher influx of returnees who need local job offers to attend to. According to the results, the labor mobility program is paramount for Salvadoran workers seeking opportunities outside their home country due to the lack of local job opportunities. Together the Salvadoran Government and key stakeholders, with support from other organizations, can provide sustainable solutions for the reintegration of these returnee labor migrants.
Thesis(Master) -- KDI School: Master of Development Poicy, 2023
Keywords: Return migration--El Salvador; Emigration and immigration--Economic aspects